TASHGĪR DALAM AL-QUR'AN: KAJIAN BENTUK DAN MAKNA DALAM AYAT-AYAT AL-QUR'AN - Sutobri, Viyan (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
This study examines the phenomenon of tashgir in the Qur'an from morphological and semantic perspectives, aiming to understand the forms and meanings embedded in the use of tashgir within the sacred text. Tashgir, as a feature of ilmu sharaf (Arabic morphology), functions not only as a grammatical device to express diminutiveness but also as a rhetorical and emotional element that enriches the Qur'anic message. This research employs a qualitative descriptive method with a linguistic approach. Primary data consists of Qur'anic verses containing tashgir, while secondary data is drawn from classical works of tafsir, nahwu, and sharaf. The results reveal that tashgir in the Qur'an serves multiple semantic functions, including: (1) diminutive physical size (e.g., ذَرَّةٍ, ٱلۡجُودِیِّ), (2) reduction of sin magnitude (اللَّمَمَ), (3) expression of affection (بُنَيّ), (4) enhancement of rhetorical effect within narratives (ٱلۡأَبۡوَٟبَ, كِتَابَهُۥ), and (5) reinforcement of moral and spiritual messages (رَجُلَيْنِ, شَيْخًا). Interpretations by classical scholars indicate that tashgir is perceived holistically in the Qur'an-not merely as a morphological process, but as a linguistic strategy imbued with theological and emotional significance. Thus, this study underscores the importance of mastering ilmu sharaf and semantic context to enrich Qur'anic interpretation.